Tourist Perception of the Quality of MSME Products and Services in Tourist Destinations - Akmal, Samsul; Zulfikri, Agung; Al-Hidayat, Rahmat; Sasmito, Priyo (West Science Journal Economic and Entrepreneurship, 2023)
This study describes tourist perceptions of the quality of MSME products and services in Ciletuh Sukabumi Geopark tourist destinations. This study used a quantitative approach with a survey method using a structured questionnaire to 200 tourist respondents visiting the Ciletuh Sukabumi Geopark. The collected data is then analyzed using descriptive analysis techniques and factor analysis to determine the factors influencing travelers' perceptions. The results showed that most respondents positively assessed the quality of MSME products and services in the Ciletuh Sukabumi Geopark. However, several aspects need to be improved, such as product quality and product variations offered. Based on factor analysis, the most influential factor on tourist perception is product quality, followed by service quality and product variety. The results of this study have significant ramifications for tourism destination managers and MSMEs in the Ciletuh Sukabumi Geopark, who want to raise the caliber of their goods and services to satisfy visitors' demands and expectations. Additionally, as part of a strategy for sustainable tourism development, this research can help policymakers in the tourism industry pay more attention to the growth of MSMEs in tourist destinations.